2022
DOI: 10.3310/nihropenres.13266.1
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the full blood count blood test and colorectal cancer detection: a longitudinal, case-control study of UK primary care patient data

Abstract: Background: The full blood count (FBC) is a common blood test performed in general practice. It consists of many individual parameters that may change over time due to colorectal cancer. Such changes are likely missed in practice. We identified trends in these FBC parameters to facilitate early detection of colorectal cancer. Methods: We performed a retrospective, case-control, longitudinal analysis of UK primary care patient data. LOWESS smoothing and mixed effects models were derived to compare trends in eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…We identified cases of CRC up until 14/01/2014 using codelists developed for the first project 13 , for practices linked to the National Cancer Registry (NCR) (clinical codes have previously been reported 15 ). An initial inspection of the capture of CRC diagnoses in CPRD indicated that linkage to the NCR would be important for high quality outcome assessment (analysis available on request).…”
Section: Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…We identified cases of CRC up until 14/01/2014 using codelists developed for the first project 13 , for practices linked to the National Cancer Registry (NCR) (clinical codes have previously been reported 15 ). An initial inspection of the capture of CRC diagnoses in CPRD indicated that linkage to the NCR would be important for high quality outcome assessment (analysis available on request).…”
Section: Outcomementioning
confidence: 99%
“…Age and sex were available for all individuals. FBC indices were extracted using CPRD Medcodes (clinical codes have previously been reported 15 ). We extracted symptom codes after searching the literature to identify symptoms associated with CRC [16][17][18][19] .…”
Section: Predictorsmentioning
confidence: 99%
“…Methods for incorporating repeated measures data into clinical decision rules are well known [ 4 ]. Our group has recently completed analyses investigating trends in multiple components of the full blood count blood test in the 10 years prior to colorectal cancer diagnosis [ 5 ]. We also developed dynamic prediction models (using joint modelling) designed for early detection of colorectal cancer, using only data earlier than 2 years before diagnosis, which incorporated trends to identify a 2-year risk of diagnosis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Methods for incorporating repeated measures data into clinical decision rules are well known 4 . Our group has recently completed analyses investigating trends in multiple components of the full blood count blood test in the ten years prior to colorectal cancer diagnosis 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Methods for incorporating repeated measures data into clinical decision rules are well known 4 . Our group has recently completed analyses investigating trends in multiple components of the full blood count blood test in the ten years prior to colorectal cancer diagnosis 5 . We also developed prediction models (using joint modelling) designed for early detection of colorectal cancer, using only data earlier than two years before diagnosis, which incorporated trends to identify two-year risk of diagnosis 6 .…”
Section: Introductionmentioning
confidence: 99%